Occupational anaphylaxis to food - Paula Olszewska; Barbara Rymarczyk; Radosław Gawlik (Medycyna Pracy)
Increasing incidence and importance of allergies in everyday life leads to bigger impact on the professional lives of patients. Continuous exposure to various allergens may be a trigger factor of development allergic diseases, even anaphylactic shock. This paper summarizes available knowledge of occupational anaphylaxis to food. This narrative literature review was based on selected, peer‑reviewed research papers, review articles and case reports between 1997–2024. The aim of the review article was to present the growing problem of allergy patients working in the food industry and to draw attention to the danger of anaphylaxis. In addition to the most popular food allergens, such as milk protein, fish, crustaceans and eggs, authors presented less popular, but becoming more important, such as crickets. Due to the increasing popularity of alternative food sources, the significance of food allergies will become more important. It is worth mentioning that occupational anaphylaxis is not only limited to the exposure to the allergen in the workplace. It can happen outside the workplace as a result of repeated exposure, after re-exposure. Med Pr Work Health Saf. 2024;75(6):521–530